Naturally Colonized Mangroves in the Digha-junput Coast, West Bengal with their Ethno-medicinal Value - Chaudhuri, Saurabh; Das, Indrani (Indian Forester, 2009)
Digha-Junput coastline of Bay of Bengal, India is unique in its own peculiar features obtained through geomorphic changes. Natural colonization of certain mangrove and halophytes on mud flat could be noticed on this coastline. An exploration was taken for search and identification of naturally colonized halophytes and mangrove medicinal plants used by the local population of Digha-Junput Coast line in West Bengal. A total of 37 species have been identified and presented along with their location of colonization, botanical names, local names, families and parts used.